Case Report: Whining toddler: could it be a serious illness - Kadam, Sandhya J.; Bongurala, Archana Reddy; Sharma, Rishika; Srivastava, Anshuman (Frontiers in Endocrinology, 2025)
Children in the developing stages whine for a variety of reasons. It can serve as a way of communicating when they cannot express their needs or feelings verbally. They may whine to seek attention or to deal with discomfort and frustration, especially when they want something but aren’t getting it quickly enough. Additionally, it can be a response to unfamiliar stress, lack of sleep, uncomfortable environment, conflicts with siblings, or separation anxiety. Whining is common in children, usually peaking in toddlers and preschoolers. Depending on how parents respond to the behavior, some children may continue to whine beyond this age. Whining can also occur in elderly patients, especially those with dementia, and may be triggered by physical pain, hunger, psychological distress, or overstimulation in their environment. Whining is usually considered a form of behavior and not a sign of illness. Ignoring it is one option recommended for dealing with it, but rarely, it could be made to signal danger, fear, pain, or some significant underlying illness. However, persistent, unexplained whining shouldn’t be simply ignored. We present a case of Type 1 diabetes mellitus with diabetic ketoacidosis (DKA), where the primary symptom was whining in a toddler who required multiple visits to the clinic and emergency department before a diagnosis was made. Whining was not initially recognized as a severe indicator of illness in this patient. To our knowledge, this is the first reported instance of newly diagnosed Type 1 diabetes mellitus with DKA in a child whose main complaint was whining.